1987
DOI: 10.1104/pp.85.4.1151
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol Specific Phospholipase C of Plant Stems

Abstract: A phosphatidylinositol-specific phospholipase C of plant stems (EC 3.1A.10) assayed at pH 6.6 and at 30°C cleaved phosphatidylinositol such that more than 85% of the product was inositol-l-phosphate. Other phospholipids were cleaved 5 to 10% or less under these conditions. The phospholipase had both a soluble and a membrane-associated form. The soluble activity accounted for approximately 85 to 90% of the activity and 15% was associated with membranes. The membrane-associated activity was most concentrated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…5). Irvine et al 33 ) have demonstrated that dialyzed soluble extracts of celery and some other plants could hydrolyze PI in the presence of Ca 2 + in the millimolar range and at neutral pH, with the release of phosphoinositol and 1,2-cyclic phosphoinositol in the ratios expected for cleavage by a phospholipase C. Pfaffmann et al 16 ) have reported that, of the total PI-PLC activity of the homogenates, approximately 85% was soluble and 15% was membrane-associated in the soybean hypocotyl, and both the soluble and the membraneassociated activities were stimulated by Ca 2 + in the same manner as total activity with an optimum of 0.5 mM. Recently, the membrane-associated PI-PLC have been characterized in various higher plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Irvine et al 33 ) have demonstrated that dialyzed soluble extracts of celery and some other plants could hydrolyze PI in the presence of Ca 2 + in the millimolar range and at neutral pH, with the release of phosphoinositol and 1,2-cyclic phosphoinositol in the ratios expected for cleavage by a phospholipase C. Pfaffmann et al 16 ) have reported that, of the total PI-PLC activity of the homogenates, approximately 85% was soluble and 15% was membrane-associated in the soybean hypocotyl, and both the soluble and the membraneassociated activities were stimulated by Ca 2 + in the same manner as total activity with an optimum of 0.5 mM. Recently, the membrane-associated PI-PLC have been characterized in various higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…19) The plasma membrane-bound PI-PLC was stimulated by a micro molar range of Ca 2 + 17 -20) and preferentially hydrolyzed PIP and PIP 2 more than pI. 16,17,19) In the rice suspension-cultured cells, most of PI-PLC activities are in the soluble fraction, but, there was little information for the soluble PI-PLC in higher plants. In this communication, we report enzymatic properties of PI-PLC purified from the soluble fraction of rice cells.…”
mentioning
confidence: 99%
“…Specifically, (a) the polyphosphoinositides must be located in the plasma membrane, (b) the enzymes responsible for the synthesis and degradation of polyphosphoinositides must be associated with the plasma membrane, (c) the polyphosphoinositide levels must transiently change upon cellular stimulation, (d) the products from the polyphosphoinositide hydrolysis must transiently increase upon stimulation, (e) a transient increase of free Ca2" in the cytosol must follow the transient increase of IP3. To date, only the first and the second criteria have been documented for several different plant tissues (15,19,25,29). There are few reports in the literature concerning polyphosphoinositide turnover in plants in response to stimuli.…”
mentioning
confidence: 99%
“…the existence of PI and PI-4-phosphate kinases (8,9,31,32) and phospholipase C (4,5,10,11,18,23,24,27,28) kinase during the growth cycle of suspension-cultured plant cells (9). In the present work the purification of DG-kinase from suspension-cultured Catharanthus roseus cells is reported and its properties are compared with enzymes described from E. coli (3,17,20,30,34) and from animal cells (14,15,19).…”
Section: Introductionmentioning
confidence: 99%
“…the existence of PI and PI-4-phosphate kinases (8,9,31,32) and phospholipase C (4,5,10,11,18,23,24,27,28), have been reported recently. We assayed the in situ activity of DG- 'This work has been supported by the Deutsche Forschungsgemeinschaft (Wa 91) and the Fonds der Chemischen Industrie.…”
mentioning
confidence: 99%